Pengaruh Pelayanan dan Daya Tarik Terhadap Minat Berkunjung ke Objek Wisata Religi di Kabupaten Jombang - Meliya Ayu Romantika; Khotim Fadhli; Moh. Ja’far Shodik Maksum (FEB Universitas Maritim Semarang, 2024)
The purpose of this study was to determine the effect of service and attractiveness on the intention to visit tourist objects in Jombang district. The method used in this research is a quantitative method. The population in this study is unlimited while the sample is 105 respondents using a purposive sampling technique. The data were collected using the questionnaire method, which were then analyzed using multiple regression analysis using SPSS version 26. The results showed that partially the service variable had an influence on the interest in visiting religious tourism objects in Jombang district, while the partial attractiveness variable also there is an influence on interest in visiting religious tourism objects in Jombang district. Simultaneously, the service and attractiveness variables affect the interest in visiting religious tourism objects in Jombang district.